FLOUTING MAXIM AS SHOWN BY CHARACTERS IN A NOVEL ENTITLED BUFFALO BILL, THE BORDER KING - I Komang Arsa Adi Winarta; Ni Wayan Suastini; I Gusti Agung Sri Rwa Jayantini (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
This study aims to determine the types of flouting maxim found in Buffalo Bill's novel and to find out the reasons for the characters to flouting the maxims. The researcher used the theory by Grice (1975) to find out the types of maxims in Buffalo Bill's novel, and Cutting (2002) theory to find out the strategies of characters in Buffalo Bill's novel violate these maxims. The data is collected from the novel Buffalo Bill, The Border King where the novel tells the reader about the life story of William F. Cody or known as Buffalo Bill during the Civil War. It was written by Colonel Ingraham and Ned Buntline and published by STREET & SMITH in 1907. The story focuses on the journey of Buffalo Bill. As a result of the analysis of research data, four types of maxim violations were committed by the characters in the novel Buffalo Bill. There is a flouting of maxim of quantity, flouting of maxim of quality, flouting of maxim of relevance, and flouting of maxim of manner. There are a total of twenty records found in Buffalo Bill's novel. flouting of maxim of quantity appears 10 times (47.7%), flouting of maxim of quality does not occur (0%), flouting of maxim of relevance appears 9 times (47.7%), and maxim of manner appears once (4,6%). In the strategy of the characters in the novel Buffalo bill violating the maxims, there are five types of causes for the characters to violate the maxims.